2021
DOI: 10.1111/1471-0528.16828
|View full text |Cite
|
Sign up to set email alerts
|

Planned mode of birth after previous caesarean section and special educational needs in childhood: a population‐based record linkage cohort study

Abstract: Objective To investigate the association between planned mode of birth after previous caesarean section and a child's risk of having a record of special educational needs (SENs).Design Population-based cohort study. Setting Scotland.Population A cohort of 44 892 singleton children born at term in Scotland between 2002 and 2011 to women with one or more previous caesarean sections.Methods Linkage of Scottish national health and education data sets.Main outcome measures Any SENs and specific types of SEN recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Greater dilation and more favorable cervical conditions were also relevant factors in studies by Maroyi et al 29 in the Democratic Republic of Congo; Fitzpatrick et al 30 , in Scotland; and Mi et al 31 , in China. These studies included women from various nationalities, featuring diverse physical and social backgrounds, along with distinct obstetric cultures.…”
Section: Discussionmentioning
confidence: 84%
“…Greater dilation and more favorable cervical conditions were also relevant factors in studies by Maroyi et al 29 in the Democratic Republic of Congo; Fitzpatrick et al 30 , in Scotland; and Mi et al 31 , in China. These studies included women from various nationalities, featuring diverse physical and social backgrounds, along with distinct obstetric cultures.…”
Section: Discussionmentioning
confidence: 84%
“…Twenty-eight were population-based studies ( 34 , 36 , 38 , 41 43 , 45 , 50 , 51 , 53 56 , 58 60 , 63 65 , 67 , 69 – 71 , 73 , 75 78 ), while 13 recruited subjects from a single ( 32 , 37 , 39 , 44 , 46 48 , 57 , 61 , 62 , 68 , 72 , 74 ) and six from multiple centers ( 33 , 35 , 40 , 49 , 52 , 66 ). Eighteen of the studies were conducted in mainland Europe ( 34 , 37 , 39 , 41 , 43 , 46 , 48 , 49 , 51 , 56 58 , 60 , 62 , 63 , 66 68 ), 10 in the United States ( 35 , 40 , 42 , 45 , 52 , 55 , 59 , 70 , 71 , 77 ), six in the United Kingdom ( 53 , 54 , 65 , 75 , 76 <...…”
Section: Resultsmentioning
confidence: 99%
“…Two population-based studies ( 54 , 76 ), both conducted in Scotland, were the only studies identified that assessed the effect of planned VBAC compared to ERCS on the child’s neurological development. One of the studies ( 54 ) reported that there was no significant difference in the risk of learning disability or cerebral palsy among around 8,000 singleton school-aged children born at term following a planned VBAC compared to an ERCS, although this study did find an increased risk of learning disability associated with repeat cesarean after an unsuccessful VBAC compared to successful VBAC (3.7% vs. 2.3%, aOR 1.64, 95% CI 1.17–2.29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing evidence suggests that while planned VBAC compared to ERCS is associated with an increased risk of various serious birth-related complications for both the woman and her baby, the absolute risk of birth-related complications is small for either birth approach [ 9 12 ]. Also, while repeat cesarean section has been linked to an increased risk of maternal complications in subsequent pregnancies such as morbidly adherent placenta [ 10 ], we have recently found little evidence to support an association between planned mode of birth after previous cesarean section and special education needs in childhood, a marker of neurodevelopmental adversity in the child [ 13 ]. However, there remains a lack of evidence about the effect of this choice on other important long-term outcomes including women’s subsequent risk of experiencing pelvic floor disorders [ 14 ].…”
Section: Introductionmentioning
confidence: 99%